PENERAPAN AKAD WADIAH PADA PRODUK SIMPANANKU DI BMT AL- AZHARI - Aries Muftie; Malihah (AD DIWAN, 2022)
The absence of divine values ​​that underlie the banking operations of other financial institutions has made this development institution a place to raise money for the powerful people who destroy the foundations of the nation's economy. Therefore, it is not too late for us as Muslim economic actors to introduce and strengthen the Islamic finance industry in Indonesia. The Indonesian population, which is predominantly Muslim, should prefer to save with a sharia contract, such as wadiah. In this regard, the author raises a study on the application of wadiah contracts at BMT Al-Azhari on simpananKu products. The contract used by BMT Al-Azhari is wadiah yad dhamanah whose withdrawal can be made at any time based on agreed terms. The writer's purpose is to find out the implementation of the wadiah contract on simpananKu products at BMT Al-Azhari, the development of SimpananKu products at BMT Al-Azhari from year to year, and find out what obstacles have been faced in simpananKu products at BMT Al-Azhari. This research is a qualitative research by interview (interview). The results of the study indicate that the wadiah yad dhamanah contract is usually applied in the form of savings which are commonly used by Islamic banks and BMTs. The implementation of the wadiah contract on simpananKu product is in accordance with Islamic law based on the DSN MUI Fatwa No. 2/DSN-MUI/IV/2000, Law no. 21 of 2008 and Circular Letter of the Financial Services Authority. The development of sales of the SimpananKu product, both from the aspect of the balance sheet, identification of customer areas, and the Covid-19 linkage has not been running perfectly, although it has increased every year but has not reached the expected target. The benefits that BMT gives to simpananKu customers will get SHU every year. simpananKu product has several obstacles, namely the absence of a debit card, the BMT Al-Azhari mobile facility which is not applied by the community, the lack of enthusiasm and awareness of students and guardians of students, and the lack of public understanding of BMT.